Mitophagy in fibrotic diseases: molecular mechanisms and therapeutic applications - Cui, Xinyan; Zhou, Zekun; Tu, Hua; Wu, Jianjun; Zhou, Jian; Yi, Qiao; Liu, Ousheng; Dai, Xiaohan (Frontiers in Physiology, 2024)
Mitophagy is a highly precise process of selective autophagy, primarily aimed at eliminating excess or damaged mitochondria to maintain the stability of both mitochondrial and cellular homeostasis. In recent years, with in-depth research into the association between mitophagy and fibrotic diseases, it has been discovered that this process may interact with crucial cellular biological processes such as oxidative stress, inflammatory responses, cellular dynamics regulation, and energy metabolism, thereby influencing the occurrence and progression of fibrotic diseases. Consequently, modulating mitophagy holds promise as a therapeutic approach for fibrosis. Currently, various methods have been identified to regulate mitophagy to prevent fibrosis, categorized into three types: natural drug therapy, biological therapy, and physical therapy. This review comprehensively summarizes the current understanding of the mechanisms of mitophagy, delves into its biological roles in fibrotic diseases, and introduces mitophagy modulators effective in fibrosis, aiming to provide new targets and theoretical basis for the investigation of fibrosis-related mechanisms and disease prevention.